Prevalence and risk-factors for Helicobacter pylori infection in urban and rural Beninese populations - Aguemon, B.D.; Struelens, M.J.; Massougbodji, A.; Ouendo, E.M. (Clinical microbiology and infection, 2005)
In total, 446 healthy individuals (240 in urban and 206 in rural environments, respectively) were selected from 96 households, based on cluster sampling of residential location. Demographic, sociological and environmental data were collected by face-to-face interviews using a standard questionnaire. Infection with Helicobacter pylori was assessed by detection of anti-H. pylori IgG serum antibodies. The prevalence of H. pylori antibodies was 75.4% in the urban population and 72.3% in rural (village) residents (p 0.459). No association was found between infection and age, gender, education level, size of household, economic activity or source of drinking water. The infection rate was higher in children whose parents were both infected, and also in children whose mother was infected (p < 0.001). By logistic regression analysis, the density of occupation of sleeping accommodation (more than three persons sharing a room; 95% odds ratio (OR) = 9.82 (4.13–23.31), p < 0.001), and the mother's status within the household (95% OR = 3.85 (1.53–9.67), p 0.003), were independent predictors for H. pylori infection. The 74% seroprevalence of H. pylori infection found in healthy Beninese individuals is similar to that reported previously from other parts of sub-Saharan Africa. Family contact with infected persons and crowded living conditions were associated with increased risk of infection. These findings are consistent with intra-familial H. pylori transmission and suggest that improvement of living conditions should be protective against infection.